Avaliação dos fatores de risco biomecânicos presentes na atividade ocupacional de eletricistas - Castro, Cristiane Shinohara Moriguchi de (2011)
Electrical energy is an essential good that may affect people s life and the economy. Overhead line workers and construction electricians are the workers responsible for the availability of this good. To perform their occupational tasks these workers are exposed to fatal accidents and musculoskeletal overload. Although of high rates of accidents and musculoskeletal injuries among these workers, few studies evaluated the presence of risk factors in the occupational settings of line workers and electricians. In this sense, it is necessary to identify the risk factors in the electricians activities (Study 1), quantify the exposure using valid direct methods (Study 2, 3 and 5) and verify the importance of the found results for clinical applications (Study 4 and 5). Study 1 was developed to determine the prevalence of musculoskeletal symptoms among line workers and to identify the risk factors for musculoskeletal disorders. The results of this study showed postural overload and high prevalence of musculoskeletal symptoms at shoulders and neck. Based on these results, Study 2 was purposed to quantify the postural overload in the five main tasks performed by line workers. Loading and unloading the ladder on the vehicle support was deeply investigated by means of posture and force measurements in Study 3, due its higher frequency in line workers schedule. Postures and movements were recorded by four inclinometer sensors at a sampling rate of 20Hz. Inclinometer sensors were previously calibrated and them attached at workers head, upper back and right and left upper arms. Study 2 and 3 identified that line workers are exposed to shoulder and neck awkward postures during all evaluated tasks. However, both studies were performed in simulated settings. By this way, Study 4 was developed to verify if the postures recorded in the simulated conditions are representative of the posture recorded in occupational environment. The results of Study 4 showed that whether the tasks are possible to be reproduced in simulated conditions the postural overload is representative of occupational overload. Besides the representativeness, Study 5 focused the comparison between posture exposure among Brazilian and Norwegian electricians to verify whether the same job type evaluated by the same method under the same procedures would present the same overload disregard the culture differences. The results of this study would allow inferring about external validity of the recordings. According to the found results, Brazilian and Norwegian posture exposure is similar. The results of Study 5 also indicated the high postural overload that these workers are submitted. Therefore, the present thesis showed the need for ergonomic interventions to reduce biomechanical risk factors presented at electricians work activity and the representativeness of the found results to occupational environmental conditions and to other populations.